Teologi Islam dalam Olahraga: Model Integrasi Keimanan bagi Atlet Muslim di Tengah Tekanan Prestasi Modern - Erus Effendi; Putri, Asmarandani Heryadi; Laksana, Muhibudin Wijaya; Solahudin, Dindin (Program Studi Pendidikan Jasmani, Fakultas Pedagogik dan Psikologi (FPeP), 2026)
Sports activities for Muslims are not merely physical exercises but also encompass a deep spiritual dimension. This study aims to identify the faith-related challenges faced by Muslim athletes in the context of modern sports and to develop an Islamic theological framework that reconciles performance excellence with sincerity. Using a qualitative descriptive approach based on library research and contextual theological analysis, this paper highlights five major issues: the obsession with winning, bodily exploitation, media-driven popularity and self-display, conflicts between worship schedules and training, and misinterpretations of fate (qadar) in victory and defeat. Based on the Qur’an and Hadith, this study proposes an Islamic Sports Theology Model that consists of five key components: tawhid, amanah, ihsan, tawakkul, and Islamic sports chaplaincy. This model provides a theological and ethical foundation for Muslim athletes to integrate faith and achievement harmoniously within the modern sports arena. Keywords: Islamic sport theology, Muslim athletes, faith and performance, bodily ethics, spiritual competition.